2022
DOI: 10.3389/fonc.2022.818868
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Lactate-Related Gene Signature for Prediction of Progression and Immunotherapeutic Response in Skin Cutaneous Melanoma

Abstract: Skin cutaneous melanoma (SKCM) is a skin cancer type characterized by a high degree of immune cell infiltration. The potential function of lactate, a main metabolic product in the tumor microenvironment (TME) of SKCM, remains unclear. In this study, we systemically analyzed the predictive value of lactate-related genes (LRGs) for prognosis and response to immune checkpoint inhibitors (ICIs) in SKCM patients included from The Cancer Genome Atlas (TCGA) database. Cluster 3, by consensus clustering for 61 LRGs, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…The effect of hypoxia on prognosis, treatment guidance, and immune infiltration assessment has been reported in many tumors, such as cervical cancer, head and neck squamous cell carcinoma, and BC (34)(35)(36). Simultaneously, lactate metabolism was related to the outcomes and immune microenvironment in skin cutaneous melanoma, kidney renal clear cell carcinoma, and BC (37)(38)(39). In BC, prognostic models have been developed solely using lactate metabolism-related genes (LMRGs) or hypoxia-related genes [HRGs] (39)(40)(41).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of hypoxia on prognosis, treatment guidance, and immune infiltration assessment has been reported in many tumors, such as cervical cancer, head and neck squamous cell carcinoma, and BC (34)(35)(36). Simultaneously, lactate metabolism was related to the outcomes and immune microenvironment in skin cutaneous melanoma, kidney renal clear cell carcinoma, and BC (37)(38)(39). In BC, prognostic models have been developed solely using lactate metabolism-related genes (LMRGs) or hypoxia-related genes [HRGs] (39)(40)(41).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggest the role of lactate metabolism-related genes in predicting tumor progression and response to immunotherapy. Xie et al demonstrated that the enhanced expression of four lactate risk-related genes, SLC25A3 , HPDL , NDUFA13 , and NARS2 , was correlated with poor prognosis in patients with skin cutaneous melanoma (SKCM), while patients with risk-related gene expression may benefit more from immune checkpoint inhibitor (ICI) therapy ( Xie et al, 2022 ). Sun et al established a lactate-related prognostic signature (LRPS) for the prognosis of patients with kidney renal clear cell carcinoma (KIRC) based on lactate metabolism-related genes and confirmed that LRPS might be effective in predicting the prognosis of patients with KIRC and that patients with low FPB1 and HDAH expression but high TYMP expression had a poor prognosis ( Sun et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In BC, lactate is correlated with resistance to PI3K inhibitors ( Hillis and TOKER, 2020 ). In several cancers, lactate is essential in predicting prognosis, tumor microenvironment, and immune response ( Mai et al, 2022 ; Sun et al, 2022 ; Xie et al, 2022 ). However, the prognostic value of lactate in BC remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown the critical value of lactate and lncRNAs in cancer classification, prognosis, and immunotherapy ( Sun et al, 2022 ; Xie et al, 2022 ; Xu et al, 2022 ). However, lactate-related lncRNAs have not been well studied in BC.…”
Section: Introductionmentioning
confidence: 99%